Integrasi Aspek Hukum, Administrasi Negara, Ekonomi, dan Akuntansi dalam Pengelolaan Hutan Mangrove Berbasis Masyarakat - Tampubolon, Khairuddin; Elazhari, Elazhari; Jenda Ingan Mahuli; Mahyudin Situmeang; Reza Hanafi Lubis; Hiya, Nirmadarningsih (Universitas Methodist Indonesia, 2024)
The purpose of writing this scientific paper is to determine the integration of multidisciplinary science in community-based mangrove forest management. The object of writing is the mangrove forest in Bagan Serdang, Pantai Labu District, Serdang Bedagai Regency. Community-based mangrove forest management is an important approach to ensure the sustainability of the ecosystem and the welfare of local communities. This scientific paper explores the integration of legal, state administration, economic, and accounting aspects in community-based mangrove forest management. By highlighting the importance of cooperation between various disciplines and compliance with regulations, this scientific paper seeks to provide a comprehensive framework for managing mangrove forests effectively and sustainably. The results of the discussion of this scientific paper are 1. The importance of the legal aspect to educate the public about the potential for conflict and customary law that applies among the community in the management of mangrove forests, 2) in the aspect of administrative science, it is necessary to accommodate the social response of the community to the regional regulations that are made, 3) The economic aspect is the need to educate the community in empowering mangrove forests in producing economic value such as ecotourism and processing of mangrove forest resources that can have economic value, 4) The accounting aspect is by suggesting the application of the mangrove kite concept, namely by involving 4 elements in the management of mangrove forests, namely: Government, Academics, Community and Private. From the results of this scientific paper, it is hoped that it can provide education to the community in optimizing the use of mangrove forests from the integration of various fields of science and will be able to provide solutions to obstacles that will occur.